2022
DOI: 10.3390/hydrogen3020014
|View full text |Cite
|
Sign up to set email alerts
|

Nanoengineering of Catalysts for Enhanced Hydrogen Production

Abstract: Hydrogen (H2) has emerged as a sustainable energy carrier capable of replacing/complementing the global carbon-based energy matrix. Although studies in this area have often focused on the fundamental understanding of catalytic processes and the demonstration of their activities towards different strategies, much effort is still needed to develop high-performance technologies and advanced materials to accomplish widespread utilization. The main goal of this review is to discuss the recent contributions in the H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 243 publications
0
14
0
Order By: Relevance
“…Considering the overpotential, Tafel slope, and turnover frequency, Seo et al found that spherical nickel phosphide nanocrystals with (001) facets had higher HER activity than rod-shaped ones with (210) facets [ 78 ]. Xiang et al produced nickel phosphide nanowires using a one-step hydrothermal method with an overpotential of 320 mV and a Tafel slope of 73 mV dec −1 for HERs [ 79 , 80 ]. Table 1 summarizes a comprehensive list of the various electrocatalysts that have been used for HER applications.…”
Section: Composite Her Electrocatalystsmentioning
confidence: 99%
“…Considering the overpotential, Tafel slope, and turnover frequency, Seo et al found that spherical nickel phosphide nanocrystals with (001) facets had higher HER activity than rod-shaped ones with (210) facets [ 78 ]. Xiang et al produced nickel phosphide nanowires using a one-step hydrothermal method with an overpotential of 320 mV and a Tafel slope of 73 mV dec −1 for HERs [ 79 , 80 ]. Table 1 summarizes a comprehensive list of the various electrocatalysts that have been used for HER applications.…”
Section: Composite Her Electrocatalystsmentioning
confidence: 99%
“…Although Proton Exchange Membrane, Solid Oxide, and Anion Exchange Membrane Electrolysis are highly studied, alkaline electrolysis achieved a more extensive commercial maturity than the other technologies [10]. It can be noticed that the method requires 1.23 V of potential for the occurrence of both the oxygen (OER) and hydrogen evolution (HER) reactions [3]. However, overpotentials are always needed, and reducing such parameters is essential once they affect the efficiency of alkaline electrolysis.…”
Section: Water Electrolysismentioning
confidence: 99%
“…This overdependence on non-renewable fuels has resulted in several environmental issues that are difficult to circumvent, such as climatic variations due to greenhouse gas emissions, poor air quality, and water/soil contamination [2]. Thus, efforts have been directed toward replacing/complementing the global carbon-based energy matrix with alternative sources, e.g., wind, solar or geothermal [3]; however, their unpredictability has considerable effects on grid operations, except when used in small amounts. In this scenario, electrochemical energy conversion technologies have received attention because they are not location-specific as the other sources, delivering higher flexibility [4].…”
Section: Introductionmentioning
confidence: 99%
“…Electrocatalytic nanomaterials have been a topic of research in the frontiers of electrochemistry, which includes their utilization in advanced applications, such as oxidation of environmental pollutants, non-enzymatic determination of organic compounds, and efficient design of fuel cells, supercapacitors, and batteries, among others. Mainly, nanostructured metal oxides based on copper, nickel, and zinc are efficient electrocatalysts when considering non-noble precursors; thus, materials based on these oxides are highly studied. Also, although some oxides find specific utilization, many applications are mutual .…”
Section: Introductionmentioning
confidence: 99%